Charting African Higher Education: Perspectives at a Glance - Teferra, Damtew (International Journal of African Higher Education, 2014)
Higher education in Africa is undergoing a transformation wrought by massive expansion, which has implications for every facet of the sector. What makes Africa’s growth unique is that it has seen a “flash flood” of growth with consequent implications that range from quality to funding, from governance to employment. Ironically, however, despite this massive growth, the system still remains the world’s least developed. This introduction to the International Journal of African Higher Education’s inaugural issue is intended to capture the state of higher education around the themes featured in this volume, based on recent as well as in-press sources. L’enseignement supérieur en Afrique connaît une transformation provoquée par une expansion massive, qui touche de nombreux aspects de ce secteur. Ce qui rend la croissance africaine unique, c’est sa rapidité qui engendre des conséquences qui vont de la qualité au financement, de la gouvernance au recrutement. Ironiquement, malgré cette croissance massive, le système reste le moins développé du monde. Cette introduction au premier numéro du Journal International sur l’Enseignement Supérieur en Afrique a pour objectif de présenter la situation de l’enseignement supérieur autour de thèmes abordés dans ce numéro. Cet article est basé sur des recherches récemment publiées ou encore sous presse.